2014
DOI: 10.1097/pec.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Recognition Program for Pediatric Services

Abstract: Improvements in care to injured children associated with the PECFR program were limited to the interval between pain assessment and pain medication for children with extremity immobilization and to radiation use 1 year after the implementation of the PECFR program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Additionally, a controlled pre-post study design of a PFR program implementation in Delaware from Ball et al reported some early and limited improvements in care to injured children. 48 More work is warranted to understand the differences between the statewide programs and how these programs impact patient outcomes within and across states for PFR. This is especially important in rural and low and medium pediatric volume EDs, which are the most likely to be underresourced for pediatric emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a controlled pre-post study design of a PFR program implementation in Delaware from Ball et al reported some early and limited improvements in care to injured children. 48 More work is warranted to understand the differences between the statewide programs and how these programs impact patient outcomes within and across states for PFR. This is especially important in rural and low and medium pediatric volume EDs, which are the most likely to be underresourced for pediatric emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Cost‐effective demonstration projects show some success for increasing pediatric readiness. For example, pediatric facility recognition programs that ensure EDs meet the minimum pediatric standards through quality improvement initiatives and onsite verification in 11 states showed improved health outcomes among pediatric patients . Simulation trainings have been a cost‐effective tool used in CAHs to improve pediatric emergency care .…”
mentioning
confidence: 99%
“…For example, pediatric facility recognition programs that ensure EDs meet the minimum pediatric standards through quality improvement initiatives and onsite verification in 11 states showed improved health outcomes among pediatric patients. [16][17][18][19][20][21] Simulation trainings have been a costeffective tool used in CAHs to improve pediatric emergency care. 22 But overall, little data exist on pediatric emergency care focusing solely on CAHs and their unique characteristics.…”
mentioning
confidence: 99%
“…The children in the state with the recognition system had improved timeliness of the management of pain for fractures and decreased exposure to radiation use. 23 Kessler et al 24 (Table 2). 11. death of a child in the ED 45, 46 ; 12. do-not-resuscitate orders; 6. a plan for the transfer of critical patient information (ie, medical record, imaging, and copy of signed transport consent) as well as personal belongings and the provision of directions and referral institution information to the family;…”
Section: Pediatric Readiness: Improving the Safety And Quality Of Pedmentioning
confidence: 98%